2022
DOI: 10.3390/jpm12071163
|View full text |Cite
|
Sign up to set email alerts
|

Association between Present Teeth and Muscle Strength in Older People in Korea

Abstract: Background: As the world population continues to age, interest in muscle strength loss in older people is increasing. This study aimed to confirm the association between present teeth and muscle strength in older people in Korea. Methods: Using data extracted from the 2014–2019 Korea National Health and Nutrition Examination Survey, we analyzed 5136 older people aged 65–79 years. The present teeth were based on 20 teeth, which is the criteria for comfortable mastication. The association of the risk of low musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…A number of studies found an association between tooth loss and relative handgrip strength [ 28 ]. The result of one study shows an association between oral hygiene maintenance and low muscular strength [ 29 ]. A study result found that handgrip strength is an established indicator of the condition of muscular strength, mainly in older individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found an association between tooth loss and relative handgrip strength [ 28 ]. The result of one study shows an association between oral hygiene maintenance and low muscular strength [ 29 ]. A study result found that handgrip strength is an established indicator of the condition of muscular strength, mainly in older individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors may be associated with age-related muscle degeneration and a decline in physical activity [ 36 ]. Tooth loss-induced malnutrition and sequential muscle protein wasting should also be considered for further study [ 37 ]. Finally, the small scale of our study in a single location means that we must be cautious about the generalizability of the results to other populations; our findings contribute to a jigsaw puzzle picture that will need to be assembled from a number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, las personas con más de 20 dientes y/o más de cinco unidades de dientes funcionales posteriores pueden masticar una gran variedad de alimentos, así como tener mayor fuerza muscular. (12,13) La ingesta adecuada de alimentos es esencial para mantener una vida saludable. La obesidad, la diabetes y otras enfermedades crónicas no transmisibles (ENT) están aumentando a nivel mundial, Pérdida de piezas dentarias y la desnutrición con una ingesta inadecuada de alimentos genera diversos problemas de salud.…”
Section: Función Masticatoria Y Edentulismounclassified